Children's illustrated encyclopedia (Noida : Om Kidz, 2021)
Children$1 (Bs illustrated encyclopedia is a visual kaleidoscope of a diverse range of subjects that the curious and sharp child is always keen to learn about. It contains the mysteries of space and Science, The wonders of our vast world, and the complexities of the human body. It also deals with the histories of amazing ancient civilisations, as well as arts and cultures- in a nutshell, it contains all that would satisfy the young mind. A must-have for the personal library!.s
Keywords: Encyclopedia